Corpus-driven insights into the discourse of women survivors of Intimate Partner Violence - Alfonso Sánchez-Moya (Quaderns de Filologia: Estudis Lingüístics, 2018)
Despite its ubiquity, Intimate Partner Violence (IPV) is still under-researched from a Critical Discourse Studies (CDS) perspective. Thus, this paper investigates the discourse of women survivors of IPV focusing on a corpus-driven examination of the data. This is done after applying the text-analysis software tool LIWC (Linguistic Inquiry and Word Count) to a 120,000-word corpus collected from an anonymised, public, online forum available to IPV survivors. I contrast a plethora of linguistic phenomena in three online communities embedded within this forum (‘Is it Abuse?’, ‘Getting out’ and ‘Life after abuse’) in the attempt to sketch out how the discursive output varies across these three stages. This paper shows how pronominal distribution plays a role in the forging of collective identity. Differences in the emotional tone across the three explored groups are also identified. Useful though these corpus-driven pointers may be, this study also warns of the precaution with which findings solely deriving from quantitative analyses need to be treated.